Native forests' destruction and illegal logging: the Argentinean case during the 1998-2016 period - Sebastián Gómez Lende (Papeles de Geografía)
Native forests’ destruction is an important environmental question that has recently accelerated not only at world scale but also in Argentina, a country where it has assumed particularly serious and disturbing features. On the basis of official, historical statistics, this paper characterizes the growth of deforestation in Argentina throughout the 1998-2016 period and studies the advance of illegal logging after the enforcement of the National Forests Law by analyzing both phenomena at the provincial and departmental scale. The findings show that almost 7 million hectares of native forests were destroyed during the analyzed period, while the annual rates of deforestation of several provinces largely exceeded the international average. In addition, due to the Nation Forests Law’s ineffectiveness, clandestine deforestation has become a widespread matter throughout the whole country, especially in provinces such as Santiago del Estero, Salta, Chaco, and Formosa.